STUDENTS’ PERCEPTION AND MOTIVATION TOWARDS ONLINE LANGUAGE LEARNING - Irhamia Irhamia (ELTIES : English Language Teaching for EFL Learners, 2021)
This research aimed at knowing the students' perception and motivation towards Online Language Learning. This research generally answered two questions as follows: (1) what is the students’ perception towards the implementation of online English Learning? and (2) what is the students’ motivation towards the implementation of online English learning? The data were collected through a questionnaire and interviews. There were 54 students of second and fourth semester at English Education Department of Universitas Islam Negeri Alauddin Makassar participated in this research. Since this research explored the students' perception and motivation which coming from the students' experiences toward online learning, descriptive qualitative design was considered as an appropriate approach as a type of research. The result of this research was presented descriptively in order to reveal the students' perception and motivation comprehensively. The research results were the students viewed positively the online language learning because it is flexible and effective. Meanwhile, its flexibility makes some students motivated but some are being lazy in doing it if they have unstable Internet connection.